Modified Repair of Interrupted Aortic Arch Utilizing Retroesophageal Right Subclavian Artery Based on a Neonatal Hybrid Approach in Hypoplastic Left Heart Complex - Valeske, Klaus; Mueller, Matthias; Hijjeh, Nizar; Boening, Andreas; Schranz, Dietmar; Akintuerk, Hakan (The Thoracic and Cardiovascular Surgeon, 2012)
Objective Interrupted aortic arch (IAA) combined with an aberrant right subclavian artery (ARSA) is frequently associated with a hypoplastic ascending aorta. Neonatal surgical therapy carries a high risk particularly for aortic arch obstructions during the further follow-up. Methods We performed a modified reconstruction of the aortic arch utilizing the ARSA as a natural substitute in a staged surgical approach. In a novel approach, the distal part of the ARSA is reimplanted into the brachiocephalic trunk. Results In three patients, a novel arch reconstruction was successfully performed during complete biventricular repair. In a follow-up of 60 to 87 months, the reconstructed aortic arch has grown without any signs of obstruction in all three patients. Conclusion Utilizing the ARSA for surgical aortic arch repair is a satisfactory solution, when postnatal borderline left heart obstruction associated with IAA and ARSA is postponed by an initial hybrid approach.
Keywords: congenital heart disease; CHD; imaging (all modalities); pediatric